Rozrolimupab, a mixture of recombinant human monoclonal anti‐D antibodies, for the treatment of primary immune thrombocytopenia – a review. (31st May 2013) - Robak, T.; Trelinski, J.; Flensburg, M. F.; Næsted, H.; Petersen, J.
<x xml:space="preserve">Abstract</x> Background In patients with immune thrombocytopenia (ITP) who are Rhesus (Rh) D positive and who have not undergone splenectomy, the platelet count can be supported by anti‐D Ig therapy. The response rate to plasma‐derived intravenous anti‐D at a dose of 50–75 μg/kg is 70–80% with an increase in platelet count after 24–72 h and duration for more than 21 days in 50% of responders. Rozrolimupab is a mixture of 25 fully human IgG1 recombinant monoclonal anti‐D antibodies produced in CHO cells using a single‐batch manufacturing strategy from a polyclonal cell bank. Materials & Methods The primary objective of the phase I/II study was to evaluate safety of a single dose in adult RhD‐positive non‐splenectomized patients with ITP. The secondary objectives were evaluations of the efficacy and appropriate dose for pivotal study. Patients were dosed with a single rozrolimupab dose ranging from 75 to 300 μg/kg, infused intravenously over 15–20 min. Results Rozrolimupab was well tolerated with no unexpected toxicities. The most frequent adverse events were headache, pyrexia, chills and fatigue. Serious adverse events were observed in nine patients, mainly in cohorts treated with doses of 200 μg/kg and 250 μg/kg, but only considered related to rozrolimupab in four patients: decrease in Hb (one patient), extravascular haemolysis (one patient) and transient increase of D‐dimers (two patients). Hb decreased by ≥3.0 g/dl in six patients, but decrease by ≥5 g/dl was not observed. Seven patients required blood transfusions. Across all cohorts, 21 of 61 patients (34%) met the response criterion on day 7. The best response was noted in the 300 μg/kg dose cohort with response observed in eight of 13 patients (62%). Median time to response was 2 days and median duration of response was 14 days. Discussion The advantage of rozrolimupab over polyclonal anti‐D immunoglobulin is unlimited supply, high and reproducible specificity and activity, and an improved safety profile. Conclusion In conclusion, our data suggest that rozrolimupab is safe, well tolerated and has efficacy similar to plasma‐derived anti‐D immunoglobulin in the treatment of primary ITP.